2012
DOI: 10.1021/jo3000282
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Diazaspiro[2.2]pentanes as a Flexible Platform for the Synthesis of Diamine-Bearing Stereotriads

Abstract: Nitrogen-containing stereotriads occur in a number of biologically active compounds, but general and flexible methods to access these compounds are limited mainly to the manipulation of chiral olefins. An alternative approach is to employ a highly chemo-, regio-, and stereocontrolled allene oxidation that can install a new carbon–heteroatom bond at each of the three original allene carbons. In this paper, an intramolecular/intermolecular allene bis-aziridination is described that offers the potential to serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…We previously leveraged the unusual strain (~42 kcal/mol) in methyleneaziridine 1a to achieve a formal [3+1] reaction to furnish methyleneazetidine 1d upon exposure to rhodium-supported carbene 1b ( Fig. 2a) [55][56][57][58][59][60][61][62] . Mechanistic studies support initial formation of the aziridinium ylide 1c, which subsequently undergoes a highly asynchronous, concerted [2,3]-Stevens rearrangement to form 1d 63 .…”
mentioning
confidence: 99%
“…We previously leveraged the unusual strain (~42 kcal/mol) in methyleneaziridine 1a to achieve a formal [3+1] reaction to furnish methyleneazetidine 1d upon exposure to rhodium-supported carbene 1b ( Fig. 2a) [55][56][57][58][59][60][61][62] . Mechanistic studies support initial formation of the aziridinium ylide 1c, which subsequently undergoes a highly asynchronous, concerted [2,3]-Stevens rearrangement to form 1d 63 .…”
mentioning
confidence: 99%
“…The successful implementation of this second‐generation synthesis required achieving a stereo‐ and regioselective aminohydroxylation to form an N,O‐aminal intermediate capable of stereoselective rearrangement to 1,3‐diaminoketone 2a . As our previous reports on the reactivity of methylene‐aziridines demonstrated that the concavity of this unusual fused heterocycle can promote highly diastereoselective reactions of the exocyclic olefin, this strategy warranted further investigation 2c…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of bicyclic MAs 189 with N-aminophthalimide in the presence of PhIO gave diazaspiro [2.2]pentane (DASP) 80 products 190 with complete facial selectivity (Scheme 54). 81 It's worth noting that the ability to electronically differentiate between the two aziridine rings of the DASPs enabled regioselective ring opening at the terminal carbon of either aziridine depending on the reaction conditions. Mostly, the addition of nucleophiles to the DASP typically favored ring-opening at C1 position to give N,N-aminal products 194 (Scheme 55).…”
Section: Reactions Of Bicyclic Masmentioning
confidence: 99%